2020
DOI: 10.1080/19490976.2020.1819155
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial bile acid metabolite skews macrophage polarization and contributes to high-fat diet-induced colonic inflammation

Abstract: Gut microbial bile acid metabolite skews macrophage polarization and contributes to high-fat dietinduced colonic inflammation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 50 publications
6
62
0
Order By: Relevance
“…As shown in Figures 4A-E, this finding supported the occurrence of damage of the ileal mucosal barrier in diabetic KKAy mice (DM group) and repaired ileal inflammatory damage after treatment with both doses of SZ-A. LPS production is also responsible for inducing monocyte-and macrophage-mediated inflammation in the intestine (Wang et al, 2020). Gut macrophages, which reside in the connective tissue underlying the gut epithelium, the lamina propria, are considered key players for the maintenance of intestinal homeostasis and inflammation (Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…As shown in Figures 4A-E, this finding supported the occurrence of damage of the ileal mucosal barrier in diabetic KKAy mice (DM group) and repaired ileal inflammatory damage after treatment with both doses of SZ-A. LPS production is also responsible for inducing monocyte-and macrophage-mediated inflammation in the intestine (Wang et al, 2020). Gut macrophages, which reside in the connective tissue underlying the gut epithelium, the lamina propria, are considered key players for the maintenance of intestinal homeostasis and inflammation (Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…4A to 4E, this nding supported the occurrence of damage of the ileal mucosal barrier in diabetic KKAy mice (DM group) and repaired ileal in ammatory damage after treatment with both doses of SZ-A. LPS production is also responsible for inducing monocyte-and macrophage-mediated in ammation in the intestine [25]. Gut macrophages, which reside in the connective tissue underlying the gut epithelium, the lamina propria, are considered key players for the maintenance of intestinal homeostasis and in ammation [26].…”
Section: Discussionsupporting
confidence: 65%
“…Among them, SCFAs were the most abundant and extensively investigated metabolites [ 58 ]. In HFD mice and DSS mice, BA was evaluated as an effective metabolic factor correlated with the gut microbiota which affects the health of the host relative to SCFAs [ 19 – 21 ]. Our results also showed that microbial change induced by LPS stimulation is deleterious to BA enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, microbiota-derived metabolites, including the endotoxin LPS, bile acids (BAs), trimethylamine N-oxide (TMAO), indolepropionic acid (IPA), and short-chain fatty acids (SCFAs), have attracted wider scientific attentions [11,[14][15][16], though SCFAs are the most common and abundant metabolites [17]. However, BAs, important endogenous molecules, have gradually been paid more attention in the field of liver diseases and intestinal inflammation [18][19][20]. Compared with SCFAs, BAs have been identified to be more relevant with gut microbiota in mice feeding on a high-fat diet (HFD) [21].…”
Section: Introductionmentioning
confidence: 99%